Epigenetic Drugs in Cognitive Disorders - Peedicayil, Jacob (Current Pharmaceutical Design, 2014)
Cognitive disorders are an important group of disorders affecting the brain for which currently used drugs are often of low efficacy and mainly of symptomatic value. There is increasing evidence suggesting that epigenetic changes in gene expression underlie cognitive disorders. Advances in epigenetics have given rise to a new class of drugs, epigenetic drugs, that reverse epigenetic changes in gene expression. At present most work on epigenetic drugs focuses on two types of drugs: histone deacetylase (HDAC) inhibitors, and drugs targeting DNA methylation. This article describes the role of epigenetic drugs in treating cognitive disorders, focusing on Alzheimer’s disease, Huntington’s disease, and Parkinson’s disease. Epigenetic drugs may improve the clinical management of patients with cognitive disorders.
Keywords: epigenetic drug